PENGARUH CITRA PERUSAHAAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN AMATARA ROYAL GANESHA HOTEL - Ni Made Puspani; I Wayan Mendra; I Gede Rihayana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2020)
Amatara Royal Ganesha Hotel is a company engaged in the field of accommodation services (Hospitality). This company prioritizes the company's image in order to survive, compete, and dominate the market share of users of tourism services, so that the company can grow and develop properly. Company image obtained by Amatara Royal Ganesha Hotel is the result of customer satisfaction appointed by employees given to customers and customer loyalty offered by the company to customers in order to fulfill their hopes and desires. This research was conducted to discuss the effect of company image and customer satisfaction on customer loyalty at Amatara Royal Ganesha. The sample in this study were 96 respondents. Determination of the sample using a simple random method. The analytical tool used is multiple linear regression analysis. The results showed that there was a positive influence on the company's image, customer satisfaction on customer loyalty.